1992
DOI: 10.1126/science.1455227
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from 12 S Ribosomal RNA Sequences that Onychophorans Are Modified Arthropods

Abstract: The evolutionary relationships of the onychophorans (velvet worms) and the monophyly of the arthropods have generated considerable debate. Cladistic analyses of 12S ribosomal RNA sequences indicate that arthropods are monophyletic and include the onychophorans. Maximum parsimony analyses and monophyly testing within arthropods indicate that myriapods (millipedes and centipedes) form a sister group to all other assemblages, whereas crustaceans (shrimps and lobsters) plus hexapods (insects and allied groups) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
113
3
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(133 citation statements)
references
References 20 publications
15
113
3
2
Order By: Relevance
“…The presence of an arthropod-type hemocyanin in the Onychophora, which is absent in other animal phyla, confirms this assumption. Molecular phylogenetic studies tend to agree on the view that the Onychophora are allied with the Euarthropoda but generally do not resolve the exact position of this taxon (27)(28)(29). Phylogenetic reconstruction of the evolution of arthropod hemocyanins using the phenoloxidases as the outgroup results in a robust tree, in which the main nodes are well supported in both neighbor-joining and maximum likelihood analyses (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…The presence of an arthropod-type hemocyanin in the Onychophora, which is absent in other animal phyla, confirms this assumption. Molecular phylogenetic studies tend to agree on the view that the Onychophora are allied with the Euarthropoda but generally do not resolve the exact position of this taxon (27)(28)(29). Phylogenetic reconstruction of the evolution of arthropod hemocyanins using the phenoloxidases as the outgroup results in a robust tree, in which the main nodes are well supported in both neighbor-joining and maximum likelihood analyses (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…A combined phylogenetic analysis, using ribosomal and nuclear protein coding genes, as well as mitochondrial genes, also places the onychophorans as a clade distinct from the Euarthropoda (Giribet et al 2001), a conclusion similarly reached by Regier et al (2005), by Mallatt et al (2004) using 28S and 18S rRNA gene sequences and by Edgecombe et al (2000) from histone H3 and U2 snRNA sequences. On the other hand, a study based on 12S ribosomal RNA sequences (Ballard et al 1992) includes Onychophora within the Euarthropoda, placing them as a sister group to the chelicerates, as does the present analysis using neural characters. The question remains whether neuroanatomical features here are sufficient to propose that the Onychophora are related to the chelicerates despite the many primitive features of the onychophoran body plan, including the paired protocerebral antennae, recently shown to be modified legs (Mayer & Koch 2005).…”
Section: Evolutionary Implicationsmentioning
confidence: 99%
“…The value of the same for 12S revealed to be higher than the other genes. Usually the 12SrRNA region is highly conserved (Ballard et al, 1992) and 16S is more variable than 12S (Hwang & Kim, 1999). Variation is extremely low at the 3'half of the molecule but it is also observed that the third domain of 12S is A+T rich and phylogenetically informative (Simon et al, 1994).…”
Section: Sequence Divergence For Various Markersmentioning
confidence: 99%